Factors Influencing the Higher Education of First-Generation Learners from Socio-Economically Disadvantaged Groups - Singh, Sunita; Kumar, Ritesh; Tigga, Ananta Ana (JOURNAL OF INDIAN EDUCATION, 2026)
Equality of educational opportunities in higher education has been a constant challenge for all. Nevertheless, the situation is rendered even more difficult for First-Generation Learners (FGLs), particularly those belonging to SocioEconomically Disadvantaged Groups (SEDGs). Data was collected from FGLs of five different central universities regarding various aspects that might affect their academic journey in higher education. The gathered data was analysed using factor analysis, and data triangulation was done through Semi-Structured Interviews and Focus Group Discussions (FGDs). The study analysed factors such as higher education goals and aspirations, urban adaptation, institutional support and environment, policy awareness and goals, financial constraints, administrative cooperation, language barriers, and overall satisfaction. It was found that the most prominent ones are financial constraints and administrative support. The study found that the higher education journey of FGLs is significantly influenced by familial financial support, along with government initiatives aimed at aiding their education. FGLs are still lacking an inclusive institutional environment, which plays a crucial role in helping them adapt, overcome mingling challenges, navigate various programmes and activities, and integrate into campus life. The study also found that technology plays an instrumental role among the FGLs in overcoming language barriers and compensating for a weak educational foundation. The study offered suggestive measures at the entry-level to provide them with specialised courses to improve their academic writing skills and overcome language barriers, followed by the mentorship programme with a supportive institutional environment and exposure towards setting their higher aspiration and valuing their culture and ethos during urban adaptation.